Cost-effective analysis of textile-reinforced mortar solutions used to reduce masonry infill walls collapse probability under seismic loads. (December 2020) - Furtado, André; Rodrigues, Hugo; Arêde, António; Varum, Humberto
Abstract: The present work aimed to perform a cost-effectiveness analysis of using textile-reinforced mortar based-solutions for strengthening masonry infill walls in the RC buildings' envelopes to reduce their OOP collapse probability. Therefore, this study starts by analyzing the effectiveness of textile-reinforced mortar based-solutions in two experimental campaigns available in the literature. Thereafter, the efficacy of the TRM is available in terms of strength, deformation and energy dissipation capacity. Influence of the textile mesh tensile strength, different types of frame-connectors and different types of mortars is discussed. The second component of this study is the cost-analysis of each TRM solution tested in these testing campaigns when compared to their efficiency during the tests. The cost of each solution is deeply analysed, estimation of the percentage of each component is computed. Finally, it is presented a case study of an 8-storey RC building structure in which its construction costs is presented according to three different locations in Portugal according to the EC8 seismic region. The costs of three different post-earthquake scenarios are analysed: i) minor damaged; b) moderate damaged; and c) extensive damages of the buildings' envelopes.